The Effect of Aerobic Exercise and Curcumin Consumption on Clinical signs and Serum Levels of sexual hormones in 18-35 year-old women with premenstrual syndrome: Randomized Clinical Trial - Ladan Zoodfekr; Hasan Matinhomai; Bahman Tarverdizadeh (Mashhad University of Medical Sciences, 2017)
Introduction: Premenstrual syndrome (PMS) occurs in the luteal phase of menstrual cycle and is severe enough to interfere with the usual aspects of the life. Aerobic exercise and herbal drugs are effective to treat PMS. This study was performed with aim to evaluate the effect of aerobic exercise and consumption of curcumin on edema, estrogen and progesterone levels in patients with PMS. Methods: This double-blind randomized clinical trial was performed on 40 women with PMS at Tabriz in 2016. The subjects were divided into 4 groups: exercise, curcumin, training + curcumin and placebo. The training groups performed aerobic exercise for 8 weeks, 3 times in a week, and the other groups daily consumed 2 capsules containing 100 mg of curcumin or placebo from 7 days before the menstrual period up to 3 first days. Diagnosis of the syndrome was done prospectively by using the Dickerson questionnaire. Data were analyzed using SPSS software (version 21) and descriptive and inferential statistics. P<0.05 was considered significant. Results: Training, curcumin and their combination had no significant effect on the edema caused by PMS, but significantly reduced physical symptoms caused by PMS (P<0.05). Improvement of behavioral symptoms of PMS was seen only in exercise group and exercise+ curcumin group (P = 0.2). PMS mood symptoms in all three groups improved compared to before and after the intervention (P<0.05). Also, none of the interventions caused significant changes in serum levels of progesterone (P>0.05). However, estrogen levels significantly decreased in all 3 groups (P<0.05). Conclusion: Both aerobic exercise and curcumin are effective in improving the symptoms and hormones of PMS, but PMS syndrome is not equally affected by these two interventions. So, it is recommended that for obtaining best results, a combination of aerobic exercise and curcumin be used in women with PMS.